Potential for biological nitrification inhibition (BNI) to reduce nitrification and N2O emissions from pasture-crop-livestock systems - Subbaraoa, Guntur V.; Rao, Idupulapati M.; Nakahara, K.; Sahrawat, Kanwar Lal; Hash, C.T.; Ando, Yasuo; Kawashima, T. (Elsevier, 2013)
Agriculture and livestock production systems are two major emitters of greenhouse gases. Methane with a GWP (global warming potential) of 21, and nitrous oxide (N2O) with a GWP of 300, are largely emitted from animal production agriculture, where livestock production is based on pasture and feed grains. The principal biological processes involved in N2O emissions are nitrification and denitrification. Biological nitrification inhibition (BNI) is the natural ability of certain plant species to release nitrification inhibitors from their roots that suppress nitrifier activity, thus reducing soil nitrification and N2O emission. Recent methodological developments (e.g. bioluminescence assay to detect BNIs in plant root systems) have led to significant advances in our ability to quantify and characterize the BNI function. Synthesis and release of BNIs from plants is a highly regulated process triggered by the presence of NH4 + in the rhizosphere, which results in the inhibitor being released precisely where the majority of the soil-nitrifier population resides. Among the tropical pasture grasses, the BNI function is strongest (i.e. BNI capacity) in Brachiaria sp. Some feed-grain crops such as sorghum also have significant BNI capacity present in their root systems. The chemical identity of some of these BNIs has now been established, and their mode of inhibitory action on Nitrosomonas has been characterized. The ability of the BNI function in Brachiaria pastures to suppress N2O emissions and soil nitrification potential has been demonstrated; however, its potential role in controlling N2O emissions in agro-pastoral systems is under investigation. Here we present the current status of our understanding on how the BNI functions in Brachiaria pastures and feed-grain crops such as sorghum can be exploited both genetically and, from a production system's perspective, to develop low-nitrifying and low N2O-emitting production systems that would be economically profitable and ecologically sustainable.